2013
DOI: 10.4322/natcon.2013.002
|View full text |Cite
|
Sign up to set email alerts
|

Going Back to Basics: Importance of Ecophysiology when Choosing Functional Traits for Studying Communities and Ecosystems

Abstract: Striking progress has been made on conceptual and methodological aspects linking species traits to community and ecosystem responses to environmental change. However, the first step when using a trait-based approach (i.e., choosing the adequate traits reflecting species response to a given environmental driver) deserves much more attention. The first broad comparative studies, using worldwide datasets, have identified a number of traits that are, for example, good indicators of plant responses to water and nut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
56
0
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(67 citation statements)
references
References 54 publications
3
56
0
7
Order By: Relevance
“…In this study we have demonstrated that a better comprehension of how tropical species from drought-prone habitats cope with changes in water availability can be based on measurements of seasonal variation in Ψ L and chlorophyll fl uorescence. These fi ndings reinforce the importance of ecophysiological knowledge when selecting functional traits for predicting responses to climate change (Rosado et al 2013), and open important avenues for models specifi cally concerning species from dry environments. In addition, because we focused on species from the Atlantic rain forest complex that are able to occupy coastal sandy plains environments, our results contribute to the understanding of the environ-mental fi ltering that affects community assembly in resource-poor habitats.…”
Section: Discussionsupporting
confidence: 60%
“…In this study we have demonstrated that a better comprehension of how tropical species from drought-prone habitats cope with changes in water availability can be based on measurements of seasonal variation in Ψ L and chlorophyll fl uorescence. These fi ndings reinforce the importance of ecophysiological knowledge when selecting functional traits for predicting responses to climate change (Rosado et al 2013), and open important avenues for models specifi cally concerning species from dry environments. In addition, because we focused on species from the Atlantic rain forest complex that are able to occupy coastal sandy plains environments, our results contribute to the understanding of the environ-mental fi ltering that affects community assembly in resource-poor habitats.…”
Section: Discussionsupporting
confidence: 60%
“…We focus on several traits which, based on the existing literature, are among the most widely used or are in urgent need of standardized measurement protocols that can be applied across taxa. From the user perspective, trait selection is often one of the crucial aspects in trait‐based approaches and it has to be based clearly bearing the research question being asked (Rosado, Dias & de Mattos ; Shipley et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…Then, data can be effectively analyzed and solutions devised through applying modeling tools, such as TOPSIS method (Zare-maivan & Memariani, 2002) and TWINSPAN and other data management programs. In this way, considering the fact that plant species interaction with environmental parameters at local level determines their community structure (abundance, diversity), scale and pattern of distribution (Hix & Pearcy, 1997) it is useful to link local adaptation strategies to global changes towards developing the tool of predicting responses (Rosado et al, 2013) to broader and comprehensive environmental changes.…”
Section: Discussionmentioning
confidence: 99%
“…Kamrani et al (2011) reported extensively on the wetland vegetation of the southern AMR and sporadic reports on arid and Irano-Touranian vegetation are available (Karimi et al, 2003;Asadi, 1988Asadi, -2008. Roodi (2009) studied the plant species richness of the N. Semnan province, Iran and documented that species of Asteraceae (12.2%), Poaceae (8.8%), Apiaceae (6.7%), Papilionaceae (6.21%), Chenopodiaceae، Brassicaceae and Labiatae (5.8%), Caryophyllaceae (5%), Rosaceae (4.2%) and Boraginaceae (4.2) were more frequent and expanding in different altitudes. Despite such reports, flora and ecophysiological aspects of vegetation of a huge area in the region still needs to be explored further.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation